Motion‐corrected simultaneous cardiac positron emission tomography and coronary MR angiography with high acquisition efficiency. Issue 1 (20th April 2017) - Munoz, Camila; Neji, Radhouene; Cruz, Gastão; Mallia, Andrew; Jeljeli, Sami; Reader, Andrew J.; Botnar, Rene M.; Prieto, Claudia
Abstract : Purpose: Develop a framework for efficient free‐breathing simultaneous whole‐heart coronary magnetic resonance angiography (CMRA) and cardiac positron emission tomography (PET) on a 3 Tesla PET‐MR system. Methods: An acquisition that enables nonrigid motion correction of both CMRA and PET has been developed. The proposed method estimates translational motion from low‐resolution 2D MR image navigators acquired at each heartbeat and 3D nonrigid respiratory motion between different respiratory bins from the CMRA data itself. Estimated motion is used for correcting the CMRA as well as the emission and attenuation PET data sets to the same respiratory position. The CMRA approach was studied in 10 healthy subjects and compared for both left and right coronary arteries (LCA, RCA) against a reference scan with diaphragmatic navigator gating and tracking. The PET‐CMRA approach was tested in 5 oncology patients with 18 F‐FDG myocardial uptake. PET images were compared against uncorrected and gated PET reconstructions. Results: For the healthy subjects, no statistically significant differences in vessel length and sharpness ( P  > 0.01) were observed between the proposed approach and the reference acquisition with navigator gating and tracking, although data acquisition was significantly shorter. The proposed approach improved CMRA vessel sharpness by 37.9% and 49.1% (LCA, RCA) and vessel length by 48.0% and 36.7% (LCA, RCA) in comparison with no motion correction for all the subjects. Motion‐corrected PET images showed improved sharpness of the myocardium compared to uncorrected reconstructions and reduced noise compared to gated reconstructions. Conclusion: Feasibility of a new respiratory motion‐compensated simultaneous cardiac PET‐CMRA acquisition has been demonstrated. Magn Reson Med 79:339–350, 2018. © 2017 The Authors Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.